Intrahippocampal injection of irisin ameliorates depression-like behaviors in mice - LI Jing, HUANG Bing-xuan, XU Qi (Jichu yixue yu linchuang, 2022)
Objective To investigate the effects of irisin on the depression-like behaviors in depression mice. Methods C57BL/6 mice were randomly divided into model and healthy groups. Mice in the model group were trained by open-space forced swim (OSFS) model and then were sub-divided into “model-control” and “model-irisin”. Healthy wild mice were bred normally and sub-divided into “healthy-control” and “healthy-irisin”groups. All mice in test group and in control groups were injected with 77 pmol irisin or the solvent (PBS) into both hippocampi by brain stereotactic injection, respectively. Depression-like behaviors were examined by forced swim test (FST) and tail suspension test (TST). Results Compared with the healthy ones, the model mice showed a markedly prolonged immobility time in FST(P＜0.01) and TST(P＜0.05), which indicated that the successfully established model can simulate the despair-like behaviors of patients with depression. Compared with the “model-control”, irisin can remarkably reduce the immobility time of “model-irisin” mice in FST(P＜0.001) and TST(P＜0.05). Conclusions Irisin can significantly improve the depression-like behaviors of OSFS depression mice.